Prediction of tropospheric wet delay by an artificial neural network model based on meteorological and GNSS data - Selbesoglu, Mahmut Oguz (ELSEVIER - DIVISION REED ELSEVIER INDIA PVT LTD, 2020)
Estimation of tropospheric wet delay is of great importance for real-time weather forecasting applications. In the last decade, based on troposphere wet delays obtained from Global Navigation Satellite System observations, high temporal and spatial resolution water vapor data can be produced for reliable and accurate weather forecasting. The main objective of this study is to investigate the accuracy of tropospheric wet delay prediction based on artificial neural network technology by the integration of Global Navigation Satellite System and meteorological data from in-situ observations of The New Austrian Meteorological Measuring Network. In the study, artificial neural network model was used to predict the wet troposphere delay up to six hour. Predicted zenith wet delay values were compared with the values estimated from Global Navigation Satellite System observations for validation. The predictions were carried out during humid (August) and dry (December) periods on two reference stations belonging to Echtzeit Positionierung Austria GNSS Network of Austria. The root mean square error of zenith wet delay prediction based on newly designed artificial neural network Model was found 1.5 cm for up to six hours. (C) 2019 Karabuk University. Publishing services by Elsevier B.V.
Keywords: GNSS meteorology; Weather forecast; Artificial neural network; Climate; Troposphere wet delay; GPS METEOROLOGY; ERRORS; Engineering